Ribonucleases and nonsense-mediated decay (NMD): An unexpected role for DIS3L2 over human NMD targets - da Costa, Paulo J. (2018)
Background: The nonsense-mediated mRNA decay (NMD) pathway selectively degrades mRNAs carrying a premature translation-termination codon but also regulates the abundance of a large number of physiological RNAs that encode full-length proteins. In human cells, NMD-targeted mRNAs are degraded by endonucleolytic cleavage and exonucleolytic degradation from both 5’ and 3’ ends. This is done by a process not yet completely understood that recruits decapping and 5’-to-3’ exonuclease activities, as well as deadenylating and 3’-to-5’ exonuclease exosome activities. In yeast, DIS3/Rrp44 protein is the catalytic subunit of the exosome, but in humans, there are three known paralogues of this enzyme: DIS3, DIS3L1, and DIS3L2. However, DIS3L2 exoribonuclease activity is independent of the exosome. DIS3L1 and DIS3L2 exoribonucleases localize in the same compartment where NMD occurs, however nothing is known about their role in this process. In order to unveil the role of DIS3L2 in NMD, we performed its knockdown in HeLa cells and measured the mRNA levels of various natural NMD targets. Our results show that some NMD targets are highly stabilized in DIS3L2-depleted cells. In addition, mRNA half-life analysis indicated that these NMD targets are in fact direct DIS3L2 substrates. We also observed that DIS3L2-mediated decay depends on the activity of the terminal uridylyl transferases (TUTases) Zcchc6/11 (TUT7/4). Together, our findings establish the role of DIS3L2 and uridylation in NMD.